Multiplier Effect of Energy Infrastructure on GRDP: Horizon in 3 Production Areas in East Kalimantan–Indonesia - Lestari, Diana; Hasid, Zamruddin; Busari, Arfiah; Ananda, Aji Alya (International Journal of Energy Economics and Policy, 2022)
The Earth is experiencing a climatic decline that exposes the degradation of the atmosphere. Unfortunately, failure to observe economic growth is not realized by developing markets, which accumulate and exhaust energy resources expansively. Therefore, this article aims to investigate the effect of electricity distribution, gas consumption, and clean water on GRDP which is addressed in three objects (Samarinda–Bontang–Balikpapan). The data interpretation technique uses panel data regression. With a time selection from 2016–2021, the results of the analysis verify several vital points, including: (1) The distribution of electricity and clean water has a positive effect and increases GRDP, but in Samarinda, the distribution of electricity has a significant impact (ρ <0.05) and clean water not significant (ρ> 0.05); (2) From Bontang, the increase in distribution of electricity and clean water also had a positive effect and significantly increased GRDP (ρ <0.05), but only gas consumption had a negative – insignificant effect on GRDP (ρ> 0.05); and (3) In Balikpapan, gas consumption has had a positive–significant impact on GRDP (ρ <0.05), where clean water gas has a positive but not significant increase in GRDP and an increase in electricity distribution has a negative–not significant impact on GRDP (ρ> 0.05). In fact, Indonesia as a nation equipped with abundant natural resources is less aware of managing and driving integrated development. That way, energy demand must be balanced with equity policies that protect the environment, restrain greed, and purify nature without overexploitation of natural resources.